Barriers effecting physical activity: Empirical study of middle aged staffs - Mohd Meerah, Abdul Rahim; Musati, Abdul Jalil; Muhammed Kassim, Rezian-na (2013)
A broad understanding of the barriers inhibiting physical activity among middle aged is critical because it affect productivity at workplace. Research stream on barriers effecting physical activity is sparse, hence this paper aims to fill the void by assessing the barriers for middle-aged staffs in participating physical activity which at a minimum recommended amount to maintain health and function.This study employed Quantitative survey method by combining a set of International Physical Activity Questionnaire (IPAQ) and Barriers Questionnaire adopted from Australian Bureau of Statistics.The participants in this cross-sectional study were 225 middle-aged Custom staff age 35 to 55 years old and randomly selected. Evidence established that the barriers to participate in physical activity among middle-aged custom employees were both effected by the internal (lacks of energy) and external (lack of time) factors. Discussions of the implication for future directions were deliberated.